ANALISA PENGARUH FASHION BATIK GONG-GONG DI KOTA BATAM TERHADAP E-WOM DENGAN MEDIASI CUSTOMER SATISFACTION - Agnes Kristy; Fitriana Aidnilla Sinambela (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2022)
Among the richness of Indonesian culture, Batik is a work of Indonesian cultural art admired by the world. Batik is an ancient art form of one of the best quality criteria. The meaning of Batik comes from the Old Javanese language, namely "amba", which means writing and "tik", which means dot. The development of Batik in the Riau Islands, which was very good, had experienced a decline because Batam tourism was closed for the past two years due to the Covid-19 pandemic, which is currently endemic. The endemic pandemic has not made MSMEs or Batam artisans sit idle. Through this, the artisans take the initiative to establish online-based sales following the times. This research is a quantitative research that examines the Analysis of Trust, Perceived Usefulness, Service Quality, Experience, and Social Media Use on Electronic Word of Mouth mediated by Customer Satisfaction at the Fashion Batik Gonggong in Batam City. Within the scope of this research, the author defines it as basic research that aims to increase knowledge that has a positive impact on science about trust, perceived usefulness, service quality, perceived experience, use of social media, electronic word of mouth, consumer satisfaction, which can be followed into comparative causal research.